Estimation and Correlation Analysis of Heavy Metals of Some Well Water in Zakho City, Iraq - Mohammad Salim, Haydar A.; Abdo, Hasan R.; Buni, Faris J.; Kareem, Idrees M.; Najeeb, Mothanna A.; Hussen, Bafreen A. (Science Journal of University of Zakho, 2017)
This study was carried out to examine the concentrations of major heavy metals in fifteen different well water in Zakho City, Kurdistan Region, Iraq. The studied heavy metals were iron, copper, chromium, aluminum, cadmium, cobalt, nickel, manganese, zinc and lead. The results obtained in the studied area showed that copper, chromium, cobalt, zinc, manganese, aluminum, iron and lead were within the acceptable limits as recommended by WHO for water drinking. However, in all studied areas, cadmium and nickel were mostly founded to exceed the maximum permissible limit set by WHO. It is found that zinc and copper possess a very good positive correlation between each other. The results obtained in this study confirmed the groundwater pollution and hence it is not suitable for consumption without any prior treatment.